Effects of porcelain layer thickness and luting resin cement on the opalescence properties of porcelain veneers - Zhemin Li; Yuchun Chen; Wanni Fu; Congchong Shi; Yunhong Lin; Jianhua Wu; Xingxing Li (BMC, 2024)
Abstract Background When discolored teeth are repaired with porcelain veneers, the thickness of the restorations should be increased appropriately using opaque porcelain and bonded by applying opaque luting resin cement to cover discolored substrates. However, its impact on the opalescent performance has not been reported yet. Purpose To analyze the effects of opacity, body porcelain layer thickness, and luting resin cement on the opalescence properties of porcelain veneer restorations for discolored teeth. Methods Ninety IPS d. SIGN A3 porcelain veneer specimens were prepared via powder-paste coating and sintering. Specimens were divided into three groups according to ceramic type and cement used or not: body porcelain group as control, body/opaque porcelain group and body/opaque porcelain-resin cement composite group. Each group was subdivided into three subgroups based on the thickness, 0.50, 0.75, and 1.00 mm (n = 10). Variolink N Bleach XL luting resin cement with thickness of 0.1 mm was applied to the bottoms of body/opaque porcelain specimens to produce body/opaque porcelain-resin cement composites. The opalescence (OP) values were calculated and the micromorphological characteristics were analyzed by scanning electron microscope (SEM). Statistical analysis was performed by using ANOVA test (P < 0.05). Results The opalescence values determined for the body porcelain groups with thicknesses of 0.50, 0.75, and 1.00 mm and body/opaque porcelain specimens with thicknesses of 0.45/0.05, 0.70/0.05, and 0.95/0.05 mm were 3.35 ± 0.15, 3.83 ± 0.10, 6.73 ± 0.25, 7.95 ± 0.34, 15.16 ± 0.60, and 16.49 ± 0.89, respectively. The specimens in the body and body/opaque porcelain groups exhibited significant increases in their opalescence values with increasing thickness (P = 0.00). The opalescence values of the specimens increased significantly with the addition of a 0.05 mm opaque porcelain layer (P = 0.00). The opalescence values of the composites containing body/opaque porcelain layers with thicknesses of 0.45/0.05, 0.70/0.05, and 0.95/0.05 mm and luting resin cement were 9.46 ± 0.17, 16.47 ± 0.15, and 18.38 ± 0.47, respectively. The opalescence values of the composite specimens increased significantly with an increase in the thickness of the porcelain layer(P = 0.00). Conclusions The opaque porcelain layer and opaque resin cement can significantly improve the opalescence properties of porcelain laminate veneers for discolored teeth, but the opalescence performance is still poor than natural teeth. The body porcelain only contributes to opalescence within a certain thickness range.